Effects of Rosiglitazon on Homocysteine and Leptin Levels in Patients with Type 2 Diabetes Mellitus Using Metformin - Özkan, Yusuf; Koca, Süleyman Serdar; Mengücük, Eylem; Gençer, Vedat; Dönder, Emir (Fırat University, 2004)
Objective: The prevalence of diabetes mellitus, a chronic progressive disease, is rising seriously. Rosiglitasone from the thiazolidinedion group is an oral antidiabetic extensively used in the treatment of type 2 DM. In this study we aimed to examine the effects of Rosiglitasone treatment on homocysteine and leptin levels. Material and method: The study included 20 voluntary patients (15 female and 5 male; mean age 51±12 years; and mean body mass index 28±5 kg/m2) who were diagnosed as type 2 DM and used Metformin, but whose blood glucose could not be regulated (high fasting blood glucose (FBG), postprandial blood glucose (PBG) and HbA1c). 4 mg/day Rosiglitasone was added to Metformin (2 x 850 mg –3 x 850 mg), which was used for treatment. FBG, PBG, HbA1c, serum lipid levels, homocysteine and leptin levels of the cases were determined before and at the end of 12-week treatment period. Results: At the end of 12-week treatment, FBG fell from 176±68 to 147±39 mg/dl (p

Amaç: Kronik ilerleyici bir hastalık olan Diabetes Mellitus'un prevalansı ciddi anlamda artmaktadır. Thiazolidinedion grubunda yer alan Rosiglitazon tip 2 DM'un tedavisinde yaygın olarak kullanılan oral antidiyabetiktir. Bu çalışmada Rosiglitazon tedavisinin homosistein ve leptin düzeyine etkilerini incelemeyi amaçladık. Gereç ve Yöntem: Tip 2 DM tanılı ve metformin kullanan ancak kan şekeri regülasyonu sağlanamayan (Açlık Kan Şekeri (AKŞ), Tokluk Kan Şekeri (TKŞ) ve HbA1c yüksek) 20 gönüllü hasta ( 5 erkek, 15 kadın, ortalama yaş 51±12 yıl ve ortalama vücut kitle indeksi 28±5 Kg/m2 olan) çalışmaya alındı. Hastaların tedavide kullandıkları metformine (2 X 850 mg – 3 X 850 mgr) 4 mg/gün roziglitazon ilave edildi. Olgularda tedavi öncesi ve 12 haftalık tedavi sonrası; AKŞ, TKŞ, HbA1c, serum lipit, homosistein ve leptin düzeyleri bakıldı. Bulgular: 12 haftalık tedavi sonrası; AKŞ 176±68 mg/dl'den, 147±39 mg/dl'ye (P
Rosiglitazonun Metformin Kullanan Tip 2 Diabetes Mellitus'lu Hastalarda Serum Homosistein Ve Leptin Düzeylerine Etkileri